Запасапие корма обыкновенной полевкой (Microtus arvalis Pall.) - Гладкина, Т.С.; Ченцова, Н.Ю. (Вестник зоологии, 1971)
The problem on manifestation of the food-storing instinct in Microtus arvalis under conditions of agricultural landscape is considered on the basis of investigations of the authors in the Kaliningrad and Leningrad regions and literature data. Large reserves of food (up to 2.5—3.3 kg of «bulbs» of Phleum pratense L.) and special depositories in some colonies on perennial herbs testify to the intensification of this instinct in Microtus arvalis in greenlands, which may favour the survival of the species in winter and its penetration to the new regions when developing the new lands.